Congenital Hypothyroidism: An Audit and Study of Different Cord Blood Screening TSH Values in a Tertiary Medical Centre in Malaysia. (27th October 2015) - Wong, Sze Lyn Jeanne; Jalaludin, Muhammad Yazid; Zaini, Azriyanti Anuar; Samingan, Nurshadia; Harun, Fatimah
Abstract : Mothers are often discharged within 24 hours in most Asian countries. Therefore, our screening programs for congenital hypothyroidism (CH) must consider the value of cord blood TSH. Our objectives were to compare the incidence of CH, positive predictive values, and recall rates using different cord blood TSH values. We also reviewed the results of the second-screening program for premature babies. 99.7% (n = 25, 757 ) of all newborns were screened from 1st January 2009 to 31st December 2013. Babies with cord blood TSH > 25 mIU/L or 20–25 mIU/L and FT4 < 20  pmol/L were recalled for a repeat venous TSH and FT4 on days 3–5 of life to confirm CH. Twenty-two babies were confirmed to have CH, an incidence of 1:1170. Five were premature. Eleven term babies had cord blood TSH > 30  mIU/L and six had values 25.1–30 mIU/L. Lowering the recall cut-off value to 20 mIU/L would double the recall rate from 0.63% (n = 163 ) to 1.3% (n = 340 ) with no additional cases detected, whereas using 30 mIU/L would have missed 35% of cases. The incidence of CH was similar, 1:1515, when using either cut-off 20 mIU/L or cut-off 25 mIU/L but lower, 1:2380, when using 30 mIU/L. We recommend the screening cord blood TSH cut-off should be 25 mIU/L and screening for premature babies should be continued.